Polycarbonate resin composition and molded article comprising same

By adding silicate minerals and phosphorus-based stabilizers to polycarbonate resin and ABS resin, the problem of insufficient fluidity and moldability of polycarbonate resin is solved, and the resin composition has high fluidity, heat resistance and Low linear expansion coefficient, suitable for a variety of industrial applications.

CN119365538APending Publication Date: 2025-01-24TEIJIN LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202380047348.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-17
Filing Date
2023-05-25
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing polycarbonate resins have shortcomings in terms of fluidity and moldability, and in the exterior parts of the automotive field, the requirements for low linear expansion coefficient are difficult to meet, and there are also challenges in impact resistance and thermal stability.

Method used

By adding a specified amount of silicate minerals to polycarbonate resin and specific ABS resin components, combining phosphorus stabilizers to optimize the composition of the resin composition to improve liquidity, heat resistance and low -line expansion coefficient.

Benefits of technology

The fluidity and thermal resistance of polycarbonate resin composition are realized, and it has a low -line expansion coefficient. It is suitable for a variety of industrial fields, especially in terms of automotive and building materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005189628040000071
    Figure BDA0005189628040000071
  • Figure BDA0005189628040000072
    Figure BDA0005189628040000072
  • Figure BDA0005189628040000081
    Figure BDA0005189628040000081
Patent Text Reader

Abstract

Provided is a polycarbonate resin composition having excellent flowability and heat resistance and having a low linear expansion coefficient. This polycarbonate resin composition is characterized by containing 5-45 parts by weight of (C) a silicate mineral (component C) per 100 parts by weight of a component comprising (A) 20-90 parts by weight of a polycarbonate resin (component A) and (B) 80-10 parts by weight of an ABS resin (component B), the content of SO4 < 2-> in the component B being 1 ppm or more, and the content of PO4 < 3-> being less than 1.5 ppm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polycarbonate resin composition and a molded article thereof, and more particularly to a polycarbonate resin composition containing a specific ABS resin and a silicate mineral, having excellent fluidity and heat resistance and a low linear expansion coefficient, and a molded article thereof. Background Art

[0002] Polycarbonate resins are widely used in industry because of their excellent mechanical and thermal properties. However, polycarbonate resins have the disadvantages of poor fluidity and poor formability due to their high melt viscosity. In order to improve the fluidity of polycarbonate resins, many polymer alloys with other thermoplastic resins have been developed. Among them, polymer alloys with styrene resins, represented by ABS resin, are widely used in the fields of OA equipment, electrical and electronic equipment, and automobiles.

[0003] In the automotive field, exterior parts such as decorative panels and spoilers need to have a low linear expansion coefficient to reduce the gap between parts, so a resin composition has been developed that contains inorganic fillers such as talc and mica in polycarbonate resin. However, due to the addition of inorganic fillers, problems such as increased specific gravity, reduced impact resistance, and silver streaks caused by reduced thermal stability occur, so improvements are needed.

[0004] For the above requirements, for example, a resin composition (patent document 1) is disclosed, which shows low linear expansion coefficient and high impact resistance by coordinating fluorine-containing resin and olefin maleic anhydride copolymer in the resin composition consisting of polycarbonate resin and talcum. However, in the case of coordinating olefin maleic anhydride copolymer in the resin composition consisting of polycarbonate resin, ABS resin and talcum, although the impact resistance is improved, there is a problem of rising linear expansion coefficient. In addition, a resin composition (patent document 2) is disclosed, which shows high impact resistance and excellent thermal stability by coordinating specific alkoxysilane compounds in the resin composition consisting of polycarbonate resin, styrene resin and inorganic filler. However, since the linear expansion coefficient depends only on the amount of inorganic filler, in order to achieve further low linear expansion, there is a problem of decreasing impact resistance and rising specific gravity.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2020-158663

[0008] Patent Document 2: Japanese Patent Application Publication No. 2004-168822 Summary of the invention

[0009] In view of the above circumstances, an object of the present invention is to provide a polycarbonate resin composition having excellent fluidity and heat resistance and a low linear expansion coefficient, and a molded article composed of the composition.

[0010] The present inventors have conducted intensive studies to solve the above problems and have found that a resin composition having excellent fluidity and heat resistance and a low linear expansion coefficient can be obtained by adding a predetermined amount of silicate mineral to a resin component composed of a polycarbonate resin and a specific ABS resin, thereby completing the present invention.

[0011] That is, the present invention is as follows.

[0012] 1. A polycarbonate resin composition, characterized in that it contains 5 to 45 parts by weight of (C) a silicate mineral (component C) relative to 100 parts by weight of a component consisting of 20 to 90 parts by weight of (A) a polycarbonate resin (component A) and 80 to 10 parts by weight of (B) an ABS resin (component B), wherein SO4 in component B is 2- The content is above 1ppm, and PO4 3- The content is less than 1.5ppm.

[0013] 2. The polycarbonate resin composition according to the above item 1, further comprising 0.001 to 1 part by weight of a phosphorus-based stabilizer (component D) based on 100 parts by weight of the components consisting of the components A and B.

[0014] 3. The aromatic polycarbonate resin composition according to item 2 above, wherein the component D is a phosphonic acid ester having an acid value of 0.01 to 0.30 mgKOH / g.

[0015] 4. The thermoplastic resin composition according to the above Item 3, wherein the component D is triethyl phosphonoacetate.

[0016] 5. A molded article made from the polycarbonate resin composition according to any one of 1 to 4 above.

[0017] The polycarbonate resin composition of the present invention has excellent fluidity and heat resistance and a low linear expansion coefficient, and is therefore widely used in housing equipment, building materials, living materials, infrastructure, automobiles, OA·EE, outdoor equipment, and other various fields. Therefore, the industrial effect of the present invention is extremely large. DETAILED DESCRIPTION

[0018] Hereinafter, the details of the present invention will be described.

[0019] <Component A: Polycarbonate resin>

[0020] The polycarbonate resin used in the present invention is obtained by reacting a dihydric phenol with a carbonate precursor. An example of the reaction method includes interfacial polymerization, melt transesterification, solid phase transesterification of carbonate prepolymers, and ring-opening polymerization of cyclic carbonate compounds.

[0021] Representative examples of the dihydric phenols used herein include hydroquinone, resorcinol, 4,4'-biphenol, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)propane (commonly known as bisphenol A), 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 2,2-bis(4-hydroxyphenyl)-3-methylphenyl)propane, 2,2-bis(4-hydroxyphenyl)- ... The preferred dihydric phenols include bis(4-hydroxyphenyl)pentane, 4,4'-(p-phenylenediisopropylidene)diphenol, 4,4'-(m-phenylenediisopropylidene)diphenol, 1,1-bis(4-hydroxyphenyl)-4-isopropylcyclohexane, bis(4-hydroxyphenyl)ether, bis(4-hydroxyphenyl)sulfide, bis(4-hydroxyphenyl)sulfoxide, bis(4-hydroxyphenyl)sulfone, bis(4-hydroxyphenyl)ketone, bis(4-hydroxyphenyl)ester, bis(4-hydroxy-3-methylphenyl)sulfide, 9,9-bis(4-hydroxyphenyl)fluorene, and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene. Preferred dihydric phenols are bis(4-hydroxyphenyl)alkanes, and among them, bisphenol A is particularly preferred from the viewpoint of impact resistance and is widely used.

[0022] In the present invention, in addition to bisphenol A-based polycarbonate resins, which are general-purpose polycarbonate-based resins, special polycarbonate-based resins produced using other dihydric phenols may be used as component A. For example, polycarbonate-based resins (homopolymers or copolymers) using 4,4'-(isophenylene diisopropylidene)diphenol (hereinafter, sometimes referred to as "BPM"), 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane (hereinafter, sometimes referred to as "Bis-TMC"), 9,9-bis(4-hydroxyphenyl)fluorene, and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene (hereinafter, sometimes referred to as "BCF") as part or all of the dihydric phenol components are suitable for applications where the requirements for dimensional change and morphological stability due to water absorption are particularly strict. It is preferred that dihydric phenols other than these BPAs be used in an amount of 5 mol% or more, particularly 10 mol% or more of the total dihydric phenol components constituting the polycarbonate-based resin. In particular, when high rigidity and better hydrolysis resistance are required, the component A constituting the resin composition is preferably a copolymerized polycarbonate resin of the following (1) to (3).

[0023] (1) A copolymerized polycarbonate resin in which, in 100 mol % of the dihydric phenol component constituting the polycarbonate resin, BPM is 20 to 80 mol % (more preferably 40 to 75 mol %, further preferably 45 to 65 mol %) and BCF is 20 to 80 mol % (more preferably 25 to 60 mol %, further preferably 35 to 55 mol %).

[0024] (2) A copolymerized polycarbonate resin in which, in 100 mol % of the dihydric phenol component constituting the polycarbonate resin, 10 to 95 mol % (more preferably 50 to 90 mol %, further preferably 60 to 85 mol %) of BPA and 5 to 90 mol % of BCF (more preferably 10 to 50 mol %, further preferably 15 to 40 mol %) of BCF are present.

[0025] (3) A copolymerized polycarbonate resin in which, in 100 mol % of the dihydric phenol component constituting the polycarbonate resin system, BPM accounts for 20 to 80 mol % (more preferably 40 to 75 mol %, and even more preferably 45 to 65 mol %) and Bis-TMC accounts for 20 to 80 mol % (more preferably 25 to 60 mol %, and even more preferably 35 to 55 mol %).

[0026] These special polycarbonate resins can be used alone or in combination of two or more thereof. In addition, they can be mixed with a general bisphenol A type polycarbonate resin. The manufacturing methods and properties of these special polycarbonate resins are described in detail in, for example, Japanese Patent Publication No. 6-172508, Japanese Patent Publication No. 8-27370, Japanese Patent Publication No. 2001-55435, and Japanese Patent Publication No. 2002-117580.

[0027] It should be noted that among the various polycarbonate resins mentioned above, the polycarbonate resins whose copolymer composition is adjusted so that the water absorption rate and Tg (glass transition temperature) are within the following ranges are particularly suitable for fields requiring morphological stability because the polymer itself has good hydrolysis resistance and is also particularly excellent in low warpage after molding.

[0028] (i) a polycarbonate resin having a water absorption of 0.05 to 0.15%, preferably 0.06 to 0.13%, and a Tg of 120 to 180°C, or

[0029] (ii) A polycarbonate resin having a Tg of 160 to 250°C, preferably 170 to 230°C, and a water absorption of 0.10 to 0.30%, preferably 0.13 to 0.30%, more preferably 0.14 to 0.27%.

[0030] Here, the water absorption of the polycarbonate resin is a value obtained by measuring the moisture content of a disk-shaped test piece having a diameter of 45 mm and a thickness of 3.0 mm after immersion in water at 23° C. for 24 hours in accordance with ISO 62-1980. In addition, Tg (glass transition temperature) is a value obtained by differential scanning calorimetry (DSC) in accordance with JIS K7121.

[0031] As the carbonate precursor, carbonyl halide, carbonic acid diester, halogenated formates, etc. can be used, and specific examples thereof include phosgene, diphenyl carbonate, and dihalogenated formates of dihydric phenols.

[0032] When utilizing interfacial polymerization to manufacture polycarbonate based resin with above-mentioned dihydric phenol and carbonate precursor, as required, can use catalyst, end-capping agent, antioxidant that is used to prevent dihydric phenol from oxidation etc.In addition, polycarbonate based resin of the present invention comprises: the branched polycarbonate based resin that is formed by copolymerization of polyfunctional aromatic compound above trifunctional, the polyester carbonate based resin that is formed by copolymerization of difunctional carboxylic acid of aromatic or aliphatic (comprising alicyclic), the copolymerization polycarbonate based resin that is formed by copolymerization of difunctional alcohol (comprising alicyclic), and the polyester carbonate based resin that is formed by copolymerization of above-mentioned difunctional carboxylic acid and difunctional alcohol.In addition, can also be the mixture that more than 2 kinds of the polycarbonate based resin that obtains are mixed into.

[0033] The branched polycarbonate resin can impart anti-drip properties to the resin composition of the present invention. Examples of the trifunctional or higher polyfunctional aromatic compound used in the branched polycarbonate resin include phloroglucinol, pentahydroxybiphenyl, or 4,6-dimethyl-2,4,6-tri(4-hydroxyphenyl)hept-2-ene, 2,4,6-trimethyl-2,4,6-tri(4-hydroxyphenyl)heptane, 1,3,5-tri(4-hydroxyphenyl)benzene, 1,1,1-tri(4-hydroxyphenyl)ethane, 1,1,1-tri(3,5-dimethyl-4-hydroxyphenyl)ethane, 2,6-bis(2-hydroxy-5-methylbenzyl)-4-methyl The present invention can be used in combination with any of the foregoing inventions and / or the invention can be used to prepare trisphenols such as 4-{4-[1,1-bis(4-hydroxyphenyl)ethyl]benzene}-α,α-dimethylbenzylphenol, tetrakis(4-hydroxyphenyl)methane, bis(2,4-dihydroxyphenyl)ketone, 1,4-bis(4,4-dihydroxytriphenylmethyl)benzene, or trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid and acid chlorides thereof. Among them, 1,1,1-tris(4-hydroxyphenyl)ethane and 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane are preferred, and 1,1,1-tris(4-hydroxyphenyl)ethane is particularly preferred.

[0034] The constituent units derived from the polyfunctional aromatic compound in the branched polycarbonate resin are preferably 0.01 to 1 mol%, more preferably 0.05 to 0.9 mol%, and further preferably 0.05 to 0.8 mol%, in the total of 100 mol% of the constituent units derived from the dihydric phenol and the constituent units derived from the polyfunctional aromatic compound. In addition, in particular, in the case of the melt transesterification method, branched structural units may be generated as a side reaction, but the amount of the branched structural units is also preferably 0.001 to 1 mol%, more preferably 0.005 to 0.9 mol%, and further preferably 0.01 to 0.8 mol%, in the total of 100 mol% of the constituent units derived from the dihydric phenol. It should be noted that the proportion of the branched structure can be adjusted by 1 It was calculated by H-NMR measurement.

[0035] The aliphatic difunctional carboxylic acid is preferably an α,ω-dicarboxylic acid. As the aliphatic difunctional carboxylic acid, for example, a straight-chain saturated aliphatic dicarboxylic acid such as sebacic acid (decane dioic acid), dodecanedioic acid, tetradecanedioic acid, octadecanedioic acid, eicosanedioic acid, and an alicyclic dicarboxylic acid such as cyclohexane dicarboxylic acid can be preferably mentioned. As the difunctional alcohol, an alicyclic diol is more preferably used, and for example, cyclohexanedimethanol, cyclohexanediol, and tricyclodecanedimethanol can be exemplified.

[0036] Reaction methods such as the interfacial polymerization method, the melt transesterification method, the carbonate prepolymer solid phase transesterification method and the ring-opening polymerization method of a cyclic carbonate compound as the production method of the polycarbonate resin of the present invention are well known in various documents and patent publications.

[0037] When the polycarbonate resin composition of the present invention is produced, the viscosity average molecular weight (M) of the polycarbonate resin is not particularly limited, but is preferably 1.6×10 4 ~4.0×10 4 , more preferably 1.7×10 4 ~3.5×10 4 , and more preferably 1.8×10 4 ~3.0×10 4 The viscosity average molecular weight is less than 1.6×10 4 When the polycarbonate resin is used, good mechanical properties may not be obtained. On the other hand, when the viscosity average molecular weight exceeds 4.0×10 4 The resin composition obtained by using a polycarbonate-based resin has poor versatility due to poor fluidity during injection molding.

[0038] It should be noted that the polycarbonate resin may be obtained by mixing a polycarbonate resin having a viscosity average molecular weight outside the above range. 4) has an increased entropy elasticity. As a result, it exhibits good molding processability in gas-assisted molding and foaming molding, which are sometimes used when molding reinforced resin materials into structural parts. The improvement in molding processability is superior to that of the branched polycarbonate resin. As a more preferred embodiment, component A may be made of a component having a viscosity average molecular weight of 7×10 4 ~3×10 5 The polycarbonate resin (component A-1-1) and the viscosity average molecular weight 1×10 4 ~3×10 4 The aromatic polycarbonate resin (component A-1-2) has a viscosity average molecular weight of 1.6×10 4 ~3.5×10 4 A polycarbonate-based resin (component A-1) (hereinafter, sometimes referred to as a "polycarbonate-based resin containing a high molecular weight component").

[0039] In the polycarbonate resin containing a high molecular weight component (component A-1), the molecular weight of component A-1-1 is preferably 7×10 4 ~2×10 5 , more preferably 8×10 4 ~2×10 5 , more preferably 1×10 5 ~2×10 5 , especially preferably 1×10 5 ~1.6×10 5 In addition, the molecular weight of component A-1-2 is preferably 1×10 4 ~2.5×10 4 , more preferably 1.1×10 4 ~2.4×10 4 , and more preferably 1.2×10 4 ~2.4×10 4 , especially preferably 1.2×10 4 ~2.3×10 4 .

[0040] The polycarbonate resin containing a high molecular weight component (component A-1) can be obtained by mixing component A-1-1 and component A-1-2 in various ratios and adjusting the ratios to satisfy a predetermined molecular weight range. Preferably, component A-1-1 accounts for 2 to 40% by weight in 100% by weight of component A-1, more preferably 3 to 30% by weight, further preferably 4 to 20% by weight, and particularly preferably 5 to 20% by weight.

[0041] In addition, examples of methods for preparing component A-1 include: (1) a method of polymerizing component A-1-1 and component A-1-2 independently and then mixing them; (2) a method of producing the above-mentioned polycarbonate-based resin in a manner satisfying the conditions of component A-1 of the present invention by a method represented by the method disclosed in Japanese Patent Application Laid-Open No. 5-306336, in which an aromatic polycarbonate resin showing a plurality of polymer peaks in a molecular weight distribution diagram based on a GPC method is produced in the same system; and (3) a method of mixing the polycarbonate-based resin obtained by the above-mentioned production method (production method (2)) with component A-1-1 and / or component A-1-2 produced separately.

[0042] The viscosity average molecular weight in the present invention is first determined by using an Ostwald viscometer from a solution prepared by dissolving 0.7 g of a polycarbonate resin in 100 ml of dichloromethane at 20° C. to obtain a specific viscosity (η) calculated from the following formula: SP ),

[0043] Specific viscosity (η SP )=(t-t0) / t0

[0044] [t0 is the falling seconds of dichloromethane, t is the falling seconds of the sample solution]

[0045] According to the calculated specific viscosity (η SP ) The viscosity average molecular weight M is calculated by the following mathematical formula.

[0046] η SP / c=[η]+0.45×[η] 2 c (where [η] is limiting viscosity)

[0047] [η] = 1.23 × 10 -4 M 0.83

[0048] c=0.7

[0049] Polycarbonate-polydiorganosiloxane copolymer resins may also be used as the polycarbonate-based resins of the present invention. The polycarbonate-polydiorganosiloxane copolymer resins are preferably copolymer resins prepared by copolymerizing a dihydric phenol represented by the following general formula (1) and a hydroxyaryl-terminated polydiorganosiloxane represented by the following general formula (3).

[0050]

[0051] [In the above general formula (1), R 1 and R 2Each independently represents a group selected from a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkyloxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group and a carboxyl group; when a plurality of each of the above groups exist, they may be the same or different; e and f are each an integer of 1 to 4; and W is at least one group selected from a single bond or a group represented by the following general formula (2).]

[0052]

[0053] [In the above general formula (2), R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 17 and R 18 Each independently represents a group selected from a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms, and R 19 and R 20 Each independently represents a group selected from a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkyloxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 10 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group and a carboxyl group. When a plurality of these groups exist, they may be the same or different. g is an integer of 1 to 10, and h is an integer of 4 to 7.]

[0054]

[0055] [In the above general formula (3), R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms, and R 9 and R 10 Each is independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, p is a natural number, q is 0 or a natural number, and p+q is a natural number from 10 to 300. X is a divalent aliphatic group having 2 to 8 carbon atoms.]

[0056] Examples of the dihydric phenol (I) represented by the general formula (1) include 4,4'-dihydroxybiphenyl, bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 2,2-bis(4-hydroxy-3,3'-biphenyl)propane, 2,2-bis(4-hydroxy-3-isopropylphenyl)propane, 2,2 bis(3-tert-butyl-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)octane, 2,2-bis(3-bromo-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 2,2-bis(3-cyclohexyl-4-hydroxyphenyl)propane, 1,1-bis(3-cyclohexyl-4-hydroxyphenyl)cyclohexane, bis(4-hydroxyphenyl)diphenylmethane, 9,9-bis(4-hydroxyphenyl)fluorene, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,1-bis(4-hydroxyphenyl)fluorene (4-Hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)cyclopentane, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxy-3,3'-dimethyl diphenyl ether, 4,4'-sulfonyl diphenol, 4,4'-dihydroxydiphenyl sulfoxide, 4,4'-dihydroxydiphenyl sulfide, 2,2'-dimethyl-4,4'-sulfonyl diphenol, 4,4'-dihydroxy-3,3'-dimethyl diphenyl sulfoxide, 4,4'-dihydroxy-3,3'-dimethyl diphenyl sulfide, 2,2'-diphenyl-4,4'-sulfonyl diphenol, 4,4 '-Dihydroxy-3,3'-diphenyl diphenyl sulfoxide, 4,4'-dihydroxy-3,3'-diphenyl diphenyl sulfide, 1,3-bis{2-(4-hydroxyphenyl)propyl}benzene, 1,4-bis{2-(4-hydroxyphenyl)propyl}benzene, 1,4-bis(4-hydroxyphenyl)cyclohexane, 1,3-bis(4-hydroxyphenyl)cyclohexane, 4,8-bis(4-hydroxyphenyl)tricyclo[5.2.1.02,6]decane, 4,4'-(1,3-adamantanediyl)diphenol, 1,3-bis(4-hydroxyphenyl)-5,7-dimethyladamantane, etc.

[0057] Among them, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 4,4'-sulfonyldiphenol, 2,2'-dimethyl-4,4'-sulfonyldiphenol, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,3-bis{2-(4-hydroxyphenyl)propyl}benzene, and 1,4-bis{2-(4-hydroxyphenyl)propyl}benzene are preferred, and 2,2-bis(4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane (BPZ), 4,4'-sulfonyldiphenol, and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene are particularly preferred. Among them, 2,2-bis(4-hydroxyphenyl)propane is most preferred because of its excellent strength and durability. In addition, these may be used alone or in combination of two or more.

[0058] As the hydroxyaryl-terminated polydiorganosiloxane represented by the general formula (3), for example, the following compounds can be suitably used.

[0059]

[0060] Hydroxyaryl-terminated polydiorganosiloxane (II) can be easily produced by subjecting phenols having ethylenically unsaturated carbon-carbon bonds, preferably vinylphenol, 2-allylphenol, isopropenylphenol, 2-methoxy-4-allylphenol, to hydrosilylation reaction with the end of a polysiloxane chain having a predetermined degree of polymerization. Among them, (2-allylphenol)-terminated polydiorganosiloxane and (2-methoxy-4-allylphenol)-terminated polydiorganosiloxane are preferred, and (2-allylphenol)-terminated polydimethylsiloxane and (2-methoxy-4-allylphenol)-terminated polydimethylsiloxane are particularly preferred. Hydroxyaryl-terminated polydiorganosiloxane (II) preferably has a molecular weight distribution (Mw / Mn) of 3 or less. In order to further exhibit excellent low outgassing properties and low-temperature impact properties during high-temperature molding, the above molecular weight distribution (Mw / Mn) is more preferably 2.5 or less, and more preferably 2 or less. If the upper limit of the above preferred range is exceeded, the amount of outgassing generated during high temperature molding may be large and the low temperature impact resistance may be poor.

[0061] In order to achieve high impact resistance, the diorganosiloxane polymerization degree (p+q) of the hydroxyaryl-terminated polydiorganosiloxane (II) is preferably 10 to 300. The diorganosiloxane polymerization degree (p+q) is preferably 10 to 200, more preferably 12 to 150, and further preferably 14 to 100. When the degree of polymerization is less than the lower limit of the preferred range, the impact resistance that is a characteristic of the polycarbonate-polydiorganosiloxane copolymer cannot be effectively exhibited, and when the degree of polymerization exceeds the upper limit of the preferred range, appearance defects occur.

[0062] The content of polydiorganosiloxane in the total weight of the polycarbonate-polydiorganosiloxane copolymer resin used in component A is preferably 0.1 to 50% by weight. The content of the polydiorganosiloxane component is more preferably 0.5 to 30% by weight, and further preferably 1 to 20% by weight. When it is above the lower limit of the preferred range, the impact resistance and flame retardancy are excellent, and when it is below the upper limit of the preferred range, a stable appearance that is not easily affected by molding conditions is easily obtained. The degree of polymerization of the polydiorganosiloxane and the content of the polydiorganosiloxane can be determined by 1 It was calculated by H-NMR measurement.

[0063] In the present invention, the hydroxyaryl-terminated polydiorganosiloxane (II) may be used alone or in combination of two or more.

[0064] Furthermore, other comonomers other than the dihydric phenol (I) and the hydroxyaryl-terminated polydiorganosiloxane (II) may be used in an amount of 10% by weight or less based on the total weight of the copolymer within a range not hindering the present invention.

[0065] In the present invention, a mixed solution containing an oligomer having a terminal chloroformate group is prepared by reacting a dihydric phenol (I) with a carbonate-forming compound in a mixed solution of a water-insoluble organic solvent and an aqueous alkali solution.

[0066] When generating the oligomer of dihydric phenol (I), the dihydric phenol (I) used in the method of the present invention can be made into oligomers all at once, or a part of it and the post-added monomer can be added as reaction raw materials in the subsequent interfacial polycondensation reaction. The post-added monomer is added in order to quickly carry out the subsequent polycondensation reaction, and does not need to be intentionally added when it is not necessary.

[0067] The method of the oligomer formation reaction is not particularly limited, but is usually preferably a method in which the reaction is carried out in a solvent in the presence of an acid binder.

[0068] The ratio of the carbonate-forming compound to be used may be appropriately adjusted in consideration of the stoichiometric ratio (equivalent) of the reaction. In the case of using a gaseous carbonate-forming compound such as phosgene, a method of blowing it into the reaction system may be appropriately adopted.

[0069] As the above-mentioned acid binder, for example, organic bases such as alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, alkali metal carbonates such as sodium carbonate, potassium carbonate, pyridine or their mixtures etc. can be used. The usage ratio of the acid binder also considers the stoichiometric ratio (equivalent) of the reaction in the same manner as above and appropriately determines. Specifically, it is preferred to use 2 equivalents or a slightly excessive acid binder compared with the mole number (usually 1 mole is equivalent to 2 equivalents) of the dihydric phenol (I) used for the formation of the oligomer.

[0070] As the above-mentioned solvent, any solvent that is inactive to various reactions such as solvents used in the manufacture of known polycarbonate resins can be used alone or as a mixed solvent. Representative examples include hydrocarbon solvents such as xylene, halogenated hydrocarbon solvents such as methylene chloride and chlorobenzene. It is particularly preferred to use halogenated hydrocarbon solvents such as methylene chloride.

[0071] The reaction pressure for oligomer formation is not particularly limited and may be any of normal pressure, pressurized, and reduced pressure. It is generally advantageous to conduct the reaction under normal pressure. The reaction temperature is selected from the range of -20 to 50°C. In many cases, heat is generated with polymerization, so water cooling or ice cooling is preferred. The reaction time is subject to other conditions and cannot be generally specified. It is generally conducted for 0.2 to 10 hours. The pH range of the oligomer formation reaction is the same as the known interfacial reaction conditions, and the pH is often prepared to be above 10.

[0072] After obtaining a mixed solution of oligomers of a dihydric phenol (I) having a terminal chloroformate group, the present invention adds a hydroxyaryl-terminated polydiorganosiloxane (II) represented by the general formula (3) which is highly purified to have a molecular weight distribution (Mw / Mn) of 3 or less to the dihydric phenol (I) while stirring the mixed solution, so that the hydroxyaryl-terminated polydiorganosiloxane (II) and the oligomer undergo interfacial polycondensation, thereby obtaining a polycarbonate-polydiorganosiloxane copolymer.

[0073]

[0074] (In the above general formula (3), R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms, R9 and R 10 Each is independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, p is a natural number, q is 0 or a natural number, and p+q is a natural number from 10 to 300. X is a divalent aliphatic group having 2 to 8 carbon atoms.

[0075] When performing the interfacial polycondensation reaction, an acid binder can be appropriately added in consideration of the stoichiometric ratio (equivalent) of the reaction. As the acid binder, for example, an alkali metal hydroxide such as sodium hydroxide, potassium hydroxide, an alkali metal carbonate such as sodium carbonate, potassium carbonate, an organic base such as pyridine, or a mixture thereof, etc. can be used. Specifically, when a part of the hydroxyaryl-terminated polydiorganosiloxane (II) or the dihydric phenol (I) as described above is added to the reaction stage as a post-addition monomer, it is preferred to use 2 equivalents of a base or an excess amount of a base relative to the total molar number (usually 1 mole is equivalent to 2 equivalents) of the dihydric phenol (I) and the hydroxyaryl-terminated polydiorganosiloxane (II) of the post-addition component.

[0076] The polycondensation by the interfacial polycondensation reaction of the oligomer of the dihydric phenol (I) and the hydroxyaryl-terminated polydiorganosiloxane (II) is carried out by vigorously stirring the mixed liquid.

[0077] In the above-mentioned polymerization reaction, an end-capping agent or a molecular weight regulator is usually used. As the end-capping agent, compounds having monophenolic hydroxyl groups can be cited, and in addition to common phenol, p-tert-butylphenol, p-cumylphenol, tribromophenol, etc., long-chain alkylphenols, aliphatic acid chlorides, aliphatic carboxylic acids, hydroxybenzoic acid alkyl esters, hydroxyphenyl alkyl esters, alkyl ether phenols, etc. can also be exemplified. The amount used is 100 to 0.5 moles, preferably 50 to 2 moles, relative to 100 moles of all diphenol compounds used. Of course, two or more compounds can also be used in combination.

[0078] In order to promote the polycondensation reaction, a catalyst such as a tertiary amine such as triethylamine or a quaternary ammonium salt may be added.

[0079] The reaction time of the above polymerization reaction is preferably 30 minutes or longer, more preferably 50 minutes or longer. A small amount of an antioxidant such as sodium sulfite or hydrogen sulfide may be added as needed.

[0080] A branching agent can be used together with the above-mentioned dihydric phenolic compound to form a branched polycarbonate-polydiorganosiloxane. Examples of the trifunctional or higher polyfunctional aromatic compound used in the above-mentioned branched polycarbonate-polydiorganosiloxane copolymer resin include phloroglucinol, pentahydroxybiphenyl, or 4,6-dimethyl-2,4,6-tri(4-hydroxyphenyl)hept-2-ene, 2,4,6-trimethyl-2,4,6-tri(4-hydroxyphenyl)heptane, 1,3,5-tri(4-hydroxyphenyl)benzene, 1,1,1-tri(4-hydroxyphenyl)ethane, 1,1,1-tri(3,5-dimethyl-4-hydroxyphenyl)ethane, 2,6-bis(2-hydroxy-5-methylbenzyl)ethane, The present invention can be used in combination with any of the following: triphenols such as tetrakis(4-hydroxyphenyl)methane, bis(2,4-dihydroxyphenyl)ketone, 1,4-bis(4,4-dihydroxytriphenylmethyl)benzene, trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid and acid chlorides thereof, among which 1,1,1-tris(4-hydroxyphenyl)ethane and 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane are preferred, and 1,1,1-tris(4-hydroxyphenyl)ethane is particularly preferred. The ratio of the multifunctional compound in the branched polycarbonate-polydiorganosiloxane copolymer resin is preferably 0.001 to 1 mol%, more preferably 0.005 to 0.9 mol%, further preferably 0.01 to 0.8 mol%, and particularly preferably 0.05 to 0.4 mol% based on the total amount of the polycarbonate-polydiorganosiloxane copolymer resin. 1 It was calculated by H-NMR measurement.

[0081] The reaction pressure may be any of reduced pressure, normal pressure, and increased pressure, and may be appropriately carried out under normal pressure or the autogenous pressure of the reaction system. The reaction temperature is selected from the range of -20 to 50°C. In many cases, heat is generated with polymerization, so water cooling or ice cooling is preferred. The reaction time varies depending on other conditions such as the reaction temperature and cannot be generally specified, but is usually carried out for 0.5 to 10 hours.

[0082] Depending on the situation, the obtained polycarbonate-polydiorganosiloxane copolymer resin may be appropriately subjected to physical treatment (mixing, classification, etc.) and / or chemical treatment (polymerization reaction, crosslinking treatment, partial decomposition treatment, etc.) to obtain a desired reduced viscosity [η SP / c] is obtained as a polycarbonate-polydiorganosiloxane copolymer resin.

[0083] The obtained reaction product (crude product) can be recovered as a polycarbonate-polydiorganosiloxane copolymer resin having a desired purity (degree of purification) by subjecting the obtained reaction product to various post-treatments such as known separation and purification methods.

[0084] The average size of the polydiorganosiloxane domain in the polycarbonate-polydiorganosiloxane copolymer resin molded product is preferably in the range of 1 to 40 nm. The above average size is more preferably 1 to 30 nm, and further preferably 5 to 25 nm. When it is less than the lower limit of the above preferred range, the impact resistance and flame retardancy cannot be fully exerted, and if it exceeds the upper limit of the above preferred range, the impact resistance may not be stably exerted. Thus, a polycarbonate resin composition with excellent impact resistance and appearance can be provided.

[0085] The average domain size of the polydiorganosiloxane domains of the polycarbonate-polydiorganosiloxane copolymer resin molded product in the present invention is evaluated by small angle X-ray scattering (SAXS). Small angle X-ray scattering refers to a method for measuring diffuse reflection and diffraction generated in a small angle region within a scattering angle (2θ) of less than 10°. In the small angle X-ray scattering method, if there are regions with different electron densities of about 1 to 100 nm in size in a substance, the diffuse scattering of X-rays is measured based on the difference in electron density. The particle size of the measured object is calculated based on the scattering angle and the scattering intensity. In the case of a polycarbonate-polydiorganosiloxane copolymer resin having a cohesive structure in which polydiorganosiloxane domains are dispersed in a matrix of a polycarbonate polymer, diffuse scattering of X-rays is generated due to the difference in electron density between the polycarbonate matrix and the polydiorganosiloxane domains. The scattering intensity I at each scattering angle (2θ) within the range of scattering angle (2θ) less than 10° is measured, and a small-angle X-ray scattering diagram is measured. The polydiorganosiloxane domain is a spherical domain, and it is assumed that there is a difference in particle size distribution. Based on the assumed particle size and the assumed particle size distribution model, a simulation is performed using commercially available analysis software to obtain the average size of the polydiorganosiloxane domain. The small-angle X-ray scattering method can measure the average size of the polydiorganosiloxane domain dispersed in the matrix of the polycarbonate polymer, which cannot be accurately measured by observation using a transmission electron microscope, with high precision, simplicity, and good reproducibility. The average domain size refers to the average value of the sizes of each domain.

[0086] The term "average domain size" used in connection with the present invention refers to a value obtained by measuring a 1.0 mm thick portion of a three-layer plate produced by the method described in the examples using the above-mentioned small angle X-ray scattering method. In addition, the analysis is performed using an independent particle model that does not consider inter-particle interactions (inter-particle interference).

[0087] <Component B: ABS resin>

[0088] The resin composition of the present invention contains ABS resin as component B. ABS resin is a copolymer obtained by grafting acrylonitrile and styrene with polybutadiene. As styrene, styrene and α-methylstyrene can be particularly preferably used. The proportion of the above-mentioned component grafted with polybutadiene is preferably 95 to 20% by weight, and particularly preferably 90 to 50% by weight in 100% by weight of the ABS resin component. In addition, relative to the total amount of 100% by weight of the above-mentioned acrylonitrile and styrene, it is preferred that acrylonitrile is 5 to 50% by weight and styrene is 95 to 50% by weight. In addition, part of the component grafted with the above-mentioned polybutadiene can also be mixed with (meth) methyl acrylate, ethyl acrylate, maleic anhydride, N-substituted maleimide, etc., and their content ratio in the ABS resin component is preferably 15% by weight or less. Further, the initiator, chain transfer agent, emulsifier, etc. used in the reaction can use various substances known in the past as needed. In the ABS resin of the present invention, the particle size of polybutadiene is preferably 0.1 to 5.0 μm, more preferably 0.2 to 3.0 μm, and particularly preferably 0.3 to 1.5 μm. The particle size distribution of the polybutadiene may be either a single distribution or a distribution having two or more peaks. In terms of morphology, the particles may be in a single phase or in a salami structure having an obstructing phase around the particles. In addition, as is known, ABS resin contains a copolymer composed of acrylonitrile and styrene not grafted to a diene rubber component, and the ABS resin of the present invention may also contain a free polymer component generated during the polymerization. The reduced viscosity of the free copolymer composed of acrylonitrile and styrene is preferably 0.2 to 1.0 dl / g, more preferably 0.3 to 0.7 dl / g, in terms of reduced viscosity (30°C). In addition, the ratio of grafted acrylonitrile and styrene to polybutadiene is preferably 20 to 200%, more preferably 20 to 70%, expressed as a grafting rate (wt%). The ABS resin can be produced by any method of bulk polymerization, suspension polymerization, and emulsion polymerization, and emulsion polymerization is particularly preferred. In addition, the copolymerization method can be a single-step copolymerization or a multi-step copolymerization. In addition, a blend of a vinyl compound polymer obtained by separately copolymerizing acrylonitrile and styrene with the ABS resin obtained by the above-mentioned production method can also be preferably used.

[0089] The content of component B is 10 to 80 parts by weight, preferably 15 to 70 parts by weight, and more preferably 20 to 60 parts by weight in 100 parts by weight of the total of components A and B. When the content of component B is less than 10 parts by weight, the fluidity becomes poor, and when it exceeds 80 parts by weight, the heat resistance decreases.

[0090] SO4 in component B 2- The content is above 1ppm, and PO4 3-The content of SO4 is less than 1.5ppm. 2- The content of PO4 is preferably 1.5 ppm or more, more preferably 2 ppm or more. 3- The content of SO4 is preferably less than 1.0 ppm, more preferably less than 0.5 ppm. 2- and PO4 3- When the content of SO4 is outside the range, the linear expansion coefficient increases. 2- The upper limit of the content of PO4 is not particularly limited, but is preferably 10 ppm or less. 3- The lower limit of the content of SO4 is not particularly limited, but is preferably 0.005 ppm or more. 2- and PO4 3- The content of is measured using an ion chromatograph in the following order. After dissolving 1 g of the ABS resin sample in 100 ml of dichloromethane, 20 ml of water is added and the mixture is shaken. Then, the mixture is allowed to stand for a while, the water layer is recovered, and ion chromatography is performed. The ion chromatography measurement can be performed using a DIONEX ion chromatograph manufactured by Dionex Corporation of Japan: Integrion HPIC RF-IC.

[0091] <Component C: Silicate mineral>

[0092] The resin composition of the present invention contains a silicate mineral as component C. Silicate minerals can use generally known silicate minerals such as wollastonite, kaolin, mica, talc, etc. The silicate mineral used as the component C of the present invention is a mineral composed of at least a metal oxide component and a SiO2 component, preferably an orthosilicate, a disilicate, a cyclic silicate, and a chain silicate. The silicate mineral takes a crystalline state, and the shape of the crystal can also take various shapes such as a fiber and a plate.

[0093] Silicate minerals may be any compound in the form of composite oxides, oxoacid salts (composed of ionic lattices), or solid solutions. In addition, composite oxides may be any combination of two or more single oxides, or any combination of two or more single oxides and oxoacid salts. In addition, solid solutions may be any solid solution of two or more metal oxides or any solid solution of two or more oxoacid salts. Silicate minerals may be hydrates. The form of crystal water in hydrates may be introduced as hydrosilicon oxide ions in the form of Si-OH, as hydroxide ions (OH - ) is introduced into the metal cation in the form of ions, and is introduced into the gaps in the structure as H2O molecules.

[0094] As the silicate mineral, an artificially synthesized product corresponding to a natural product may be used. As the artificially synthesized product, a silicate mineral obtained by various conventionally known methods, for example, various synthesis methods utilizing solid state reaction, hydrothermal reaction, and ultrahigh pressure reaction may be used.

[0095] Specific examples of silicate minerals in each metal oxide component (MO) include the following: Here, the description in parentheses is the name of a mineral or the like containing the above-mentioned silicate mineral as a main component, and means that the compound in the parentheses can be used as an exemplified metal salt.

[0096] Examples of silicate minerals containing K2O as a component include K2O·SiO2, K2O·4SiO2·H2O, K2O·Al2O3·2SiO2 (potassium pyroxene), K2O·Al2O3·4SiO2 (leucite), and K2O·Al2O3·6SiO2 (orthoclase).

[0097] Examples of silicate minerals whose components include Na2O include Na2O·SiO2, and its hydrates, Na2O·2SiO2, 2Na2O·SiO2, Na2O·4SiO2, Na2O·3SiO2·3H2O, Na2O·Al2O3·2SiO2, Na2O·Al2O3·4SiO2 (pyroxene), 2Na2O·3CaO·5SiO2, 3Na2O·2CaO·5SiO2, and Na2O·Al2O3·6SiO2 (albite), etc.

[0098] Examples of silicate minerals whose components include Li2O include Li2O·SiO2, 2Li2O·SiO2, Li2O·SiO2·H2O, 3Li2O·2SiO2, Li2O·Al2O3·4SiO2 (petalite), Li2O·Al2O3·2SiO2 (eucryptite) and Li2O·Al2O3·4SiO2 (spodumene).

[0099] Examples of silicate minerals containing BaO as a component include BaO.SiO 2 , 2BaO.SiO 2 , BaO.Al 2 O 3 .2SiO 2 (barium feldspar), and BaO.TiO 2 .3SiO 2 (bentonite).

[0100] Examples of silicate minerals containing CaO as a component thereof include 3CaO·SiO2 (tricalcium silicate of cement clinker mineral), 2CaO·SiO2 (dicalcium silicate of cement clinker mineral), 2CaO·MgO·2SiO2 (magnesium calcite), 2CaO·Al2O3·SiO2 (calcium aluminum calcite), a solid solution of magnesium calcite and calcite (calcite), CaO·SiO2 (wollastonite (including both α-type and β-type)), CaO·MgO·2SiO2 (diopside), CaO·MgO·SiO2 (calcium olivine), 3CaO·MgO·2SiO2 (magnesium calcite), CaO·Al2O3·2SiO2 (calcium feldspar), 5CaO·6SiO2·5H2O (tobermorite, 5CaO·6SiO2·9H2O, etc.) and other hydrated tobermorite groups. hydrates of wollastonite such as 2CaO·SiO2·H2O (calcite), hydrates of wollastonite such as 6CaO·6SiO2·H2O (xonotlite), hydrates of whitsonite such as 2CaO·SiO2·2H2O (white calcium zeolite), CaO·Al2O3·2SiO2·H2O (hard calcium zeolite), CaO·FeO·2SiO2 (ferrocalcium pyroxene), 3CaO·2SiO 2 (brown zircon), 3CaO·Al2O3·3SiO2 (grossular garnet), 3CaO·Fe2O3·3SiO2 (andradite), 6CaO·4Al2O3·FeO·SiO2 (pleochroite), as well as clinzoisite, carnelian, allantois, fenghuang stone, axestone, scroosite and common pyroxene.

[0101] In addition, as a silicate mineral containing CaO as a component, Portland cement can be cited. The type of Portland cement is not particularly limited, and any of ordinary, early strength, super early strength, medium heat, sulfate-resistant, white, etc. can be used. Various mixed cements such as blast furnace cement, silica cement, fly ash cement, etc. can also be used as the C component.

[0102] In addition, examples of materials containing other CaO as components include blast furnace slag, ferrite, and the like.

[0103] Examples of silicate minerals containing ZnO as a component include ZnO·SiO 2 , 2ZnO·SiO 2 (sonite), and 4ZnO·2SiO 2 ·H 2 O (hemimorphite).

[0104] Examples of silicate minerals containing MnO as a component include MnO·SiO 2 , 2MnO·SiO 2 , CaO·4MnO·5SiO 2 (rhodonite) and salviaemin.

[0105] Examples of silicate minerals containing FeO as a component include FeO·SiO2 (orthopyroxene), 2FeO·SiO2 (fayalite), 3FeO·Al2O3·3SiO2 (aluminum garnet) and 2CaO·5FeO·8SiO2·H2O (ferroactinolite).

[0106] Examples of silicate minerals containing CoO as a component include CoO·SiO 2 and 2CoO·SiO 2 .

[0107] Examples of silicate minerals containing MgO include MgO·SiO2 (talc, enstatite), 2MgO·SiO2 (forsterite), 3MgO·Al2O3·3SiO2 (pyrope), 2MgO·2Al2O3·5SiO2 (cordierite), 2MgO·3SiO2·5H2O, 3MgO·4SiO2·H2O (talc), 5MgO·8SiO2·9H2O (attapulgite), 4MgO·6SiO2·7 H2O (sepiolite), 3MgO·2SiO2·2H2O (chrysolite), 5MgO·2CaO·8SiO2·H2O (tremolite), 5MgO·Al2O3·3SiO2·4H2O (chlorite), K2O·6MgO·Al2O3·6SiO2·2H2O (phlogopite), Na2O·3MgO·3Al2O3·8SiO2·H2O (glaucophane), as well as magnesia tourmaline, anthophyllite, ferromagnesian amphibole, vermiculite, montmorillonite, etc.

[0108] Examples of silicate minerals containing Fe2O3 as a component include Fe2O3·SiO2 and the like.

[0109] Examples of silicate minerals containing ZrO 2 as a component include ZrO 2 ·SiO 2 (zircon) and AZS refractory materials.

[0110] Examples of silicate minerals whose components contain Al2O3 include Al2O3·SiO2 (sillimanite, andalusite, kyanite), 2Al2O3·SiO2, Al2O3·3SiO2, 3Al2O3·2SiO2 (mullite), Al2O3·2SiO2·2H2O (kaolinite), Al2O3·4SiO2·H2O (phyllite), Al2O3·4SiO2·H2O (bentonite), K2O·3Na2O·4Al2O3·8SiO2 (nepheline), K2O·3Al2O3·6SiO2·2H2O (dolomite, sericite), K2O·6MgO·Al2O3·6SiO2·2H2O (phlogopite), various zeolites, fluorphlogopite and biotite, etc.

[0111] Among the above-mentioned silicate minerals, mica, talc and wollastonite are particularly preferred, and at least one silicate mineral including talc is particularly preferred.

[0112] (talc)

[0113] The talc in the present invention is a hydrous magnesium silicate in chemical composition, generally represented by the chemical formula 4SiO2·3MgO·2H2O, and is usually a flaky particle with a layered structure. In addition, in terms of composition, it is composed of 56-65% by weight of SiO2, 28-35% by weight of MgO, and about 5% by weight of H2O. As other minor components, it contains 0.03-1.2% by weight of Fe2O3, 0.05-1.5% by weight of Al2O3, 0.05-1.2% by weight of CaO, 0.2% or less of K2O, and 0.2% or less of Na2O. The particle size of the talc is preferably in the range of 0.1-15μm (more preferably 0.2-12μm, further preferably 0.3-10μm, and particularly preferably 0.5-5μm) as an average particle size measured by a sedimentation method. Furthermore, it is particularly preferred to use a bulk density of 0.5 (g / cm 3 ) or more talc as raw material. The average particle size of talc refers to the D50 (median particle size of particle size distribution) measured by X-ray transmission method as one of liquid phase sedimentation methods. As a specific example of the device for performing the above measurement, Sedigraph5100 made by Micromeritics Company can be cited.

[0114] In addition, the manufacturing method when pulverizing talc from the rough stone is not particularly limited, and axial flow mill, ring mill, roller mill, ball mill, jet mill and container rotary compression shearing mill etc. can be utilized. And then, the talc after pulverization is preferably subjected to classification treatment by various classifiers to make the distribution of particle size consistent. As classifier, there is no particular restriction, and impact inertial force classifier (variable impact machine etc.), Coanda effect inertial force classifier (elbow jet machine etc.), centrifugal field classifier (multi-stage cyclone, micro-classifier (MicroPlex), dispersion classifier, AccuCut classifier (AccuCut), eddy current classifier, turbine wind classifier (TurboPlex), airflow classifier and super classifier etc.) etc. can be cited. In addition, talc is preferably in a coagulated state in terms of its handling properties, and as the above-mentioned manufacturing method, there are methods utilizing degassing compression, methods utilizing sizing agent to compress etc.. From the viewpoint that the simple and unnecessary sizing agent resin component is not mixed in the resin composition of the present invention, it is particularly preferred to utilize the method utilizing degassing compression.

[0115] (Mica)

[0116] Mica can preferably have an average particle size of 10 to 100 μm as measured by Microtrack diffraction method. More preferably, mica has an average particle size of 20 to 50 μm. When the average particle size of mica is less than 10 μm, the improvement effect on rigidity is insufficient. Even if it exceeds 100 μm, the improvement in rigidity is insufficient, and sometimes the reduction in mechanical strength such as impact characteristics is also obvious, so it is not preferred. Mica can preferably use mica with a thickness of 0.01 to 1 μm measured by observation under an electron microscope. More preferably, the thickness is 0.03 to 0.3 μm. In terms of aspect ratio, mica preferably has a value of 5 to 200, and more preferably 10 to 100. In addition, the mica used is preferably muscovite, and its Mohs hardness is about 3. Compared with other micas such as phlogopite, muscovite can achieve higher rigidity and higher strength, and solve the subject of the present invention at a better level. In addition, as a mica pulverization method, it can be manufactured by any method of dry pulverization method and wet pulverization method. The dry pulverization method is generally low-cost, while the wet pulverization method is effective in pulverizing mica into thinner and finer particles, and as a result, the rigidity of the resin composition is further improved.

[0117] (Wollastonite)

[0118] The fiber diameter of wollastonite is preferably 0.1 to 10 μm, more preferably 0.1 to 5 μm, and further preferably 0.1 to 3 μm. In addition, its aspect ratio (average fiber length / average fiber diameter) is preferably 3 or more. As the upper limit of the aspect ratio, 30 or less can be cited. Here, the fiber diameter is obtained by observing the reinforcing filler with an electron microscope, and the diameter of each fiber is obtained, and the number average fiber diameter is calculated from the measured value. The electron microscope is used because it is difficult to accurately measure the size of the level as the object using an optical microscope. The fiber diameter is to randomly extract the filler of the object for measuring the fiber diameter from the image obtained by observation of the electron microscope, measure the fiber diameter near the central part, and calculate the number average fiber diameter from the obtained measured value. The observation magnification is about 1000 times, and the number of roots is measured for more than 500 (600 or less is suitable for operation). On the other hand, the average fiber length is measured by observing the filler with an optical microscope, and each length is obtained, and the number average fiber length is calculated based on its measured value. The observation under the optical microscope is started after preparing the sample dispersed in a way that the fillers are basically not overlapped with each other. The observation is carried out under the condition of 20 times the objective lens, and the observed image is imported into a CCD camera with a pixel number of about 250,000 in the form of image data. The image data obtained is used by an image analysis device, and the fiber length is calculated using a program that calculates the maximum distance between two points of the image data. Under the above conditions, the size of each pixel is equivalent to a length of 1.25μm, and the number of roots is measured to be more than 500 (less than 600 roots are suitable for operation).

[0119] In order to fully reflect the whiteness of the wollastonite of the present invention in the resin composition, it is preferred to use a magnetic separator to remove as much iron as possible that is mixed into the raw material ore and iron that is mixed into the raw material ore due to machine wear when the raw material ore is crushed. After the above-mentioned magnetic separator treatment, the iron content in the wollastonite is preferably 0.5% by weight or less in terms of Fe2O3.

[0120] Silicate minerals (more preferably mica, talc, wollastonite) are preferably not surface treated, but may be surface treated with various surface treatment agents such as silane coupling agents, higher fatty acid esters, and waxes. In addition, various resins, higher fatty acid esters, and waxes may be used to granulate the granules.

[0121] The content of component C is 5 to 45 parts by weight, preferably 8 to 40 parts by weight, and more preferably 10 to 35 parts by weight relative to 100 parts by weight of the components consisting of components A and B. When the content of component C is less than 5 parts by weight, a sufficient linear expansion coefficient cannot be obtained, and when it exceeds 45 parts by weight, extrusion becomes difficult.

[0122] <Component D: Phosphorus stabilizer>

[0123] The resin composition of the present invention preferably contains a phosphorus stabilizer as component D. As the phosphorus stabilizer, phosphorous acid, phosphoric acid, phosphonous acid, phosphonic acid and their esters, and tertiary phosphine can be used, preferably phosphonate. As the phosphonate, phosphonate monoesters, phosphonate diesters, and phosphonate triesters can be used, preferably phosphonate triesters. The number of carbon atoms of the ester can be used in various combinations within 1 to 22, and triethyl phosphonoacetate is most preferred. The acid value of the phosphonate is preferably 0.01 to 0.30 mgKOH / g, more preferably 0.01 to 0.20 mgKOH / g, and further preferably 0.05 to 0.15 mgKOH / g. Phosphonates with an acid value of less than 0.01 mgKOH / g are not practical in production, and when greater than 0.30 mgKOH / g, appearance defects such as silver streaks sometimes occur. The acid value is determined using a potentiometric titration apparatus, and the alcohol solution of the phosphonate is titrated with a KOH alcohol solution.

[0124] The content of component D is preferably 0.001 to 1 part by weight, more preferably 0.01 to 0.1 part by weight, and further preferably 0.01 to 0.07 part by weight relative to 100 parts by weight of the components consisting of components A and B. When the content of component B is less than 0.001 parts by weight, appearance defects such as silver streaks may sometimes occur. On the other hand, since the effect is fully exerted at less than 1 part by weight, the cost may increase when the content exceeds 1 part by weight.

[0125] <Other ingredients>

[0126] The resin composition of the present invention may also contain a phenolic stabilizer, a mold release agent, an ultraviolet absorber, a core-shell type graft polymer, a dye, a pigment (carbon black, titanium oxide, etc.), and the like.

[0127] (i) Phenolic stabilizers and other heat stabilizers

[0128] The resin composition of the present invention may be formulated with various heat stabilizers other than phosphorus stabilizers, represented by phenolic stabilizers such as hindered phenol compounds. As hindered phenol compounds, various compounds usually formulated in resins may be used. Examples of the hindered phenol compounds include α-tocopherol, butylhydroxytoluene, sinapyl alcohol, vitamin E, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 2-tert-butyl-6-(3'-tert-butyl-5'-methyl-2'-hydroxybenzyl)-4-methylphenyl acrylate, 2,6-di-tert-butyl-4-(N,N-dimethylaminomethyl)phenol, 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid diethyl ester, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-methylenebis(2,6-di-tert-butylphenol), 2,2' -Methylenebis(4-methyl-6-cyclohexylphenol), 2,2'-dimethylenebis(6-α-methyl-benzyl-p-cresol), 2,2'-ethylenebis(4,6-di-tert-butylphenol), 2,2'-butylenebis(4-methyl-6-tert-butylphenol), 4,4'-butylenebis(3-methyl-6-tert-butylphenol), triethylene glycol-N-bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate, 1,6-hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], bis[2-tert-butyl-4-methyl-6-(3-tert-butyl-5-methyl-2-hydroxybenzyl)phenyl]terephthalate, 3 ,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro[5,5]undecane, 4,4'-thiobis(6-tert-butyl-m-cresol), 4,4'-thiobis(3-methyl-6-tert-butylphenol), 2,2'-thiobis(4-methyl-6-tert-butylphenol), bis(3,5-di-tert-butyl-4-hydroxybenzyl)sulfide, 4,4'-dithiobis(2,6-di-tert-butylphenol), 4,4'-trithiobis(2,6-di-tert-butylphenol), 2,2-thiodiethylenebis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro[5,5]undecane ) propionate], 2,4-bis(n-octylthio)-6-(4-hydroxy-3,5-di-tert-butylanilino)-1,3,5-triazine, N,N'-hexamethylenebis-(3,5-di-tert-butyl-4-hydroxyhydrocinnamic acid), N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tris(3,5-di-tert-butyl-4-hydroxyphenyl) isocyanurate, tris(3,5-di-tert-butyl-4-hydroxybenzyl) isocyanurate, 1,3,5-Tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl) isocyanurate, 1,3,5-tris-2[3(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxy]ethyl isocyanurate, tetrakis[methylene-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]methane, triethylene glycol-N-bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate, triethylene glycol-N-bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl) acetate , 3,9-bis[2-{3-(3-tert-butyl-4-hydroxy-5-methylphenyl)acetoxy}-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5,5]undecane, tetrakis[methylene-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate]methane, 1,3,5-trimethyl-2,4,6-tri(3-tert-butyl-4-hydroxy-5-methylbenzyl)benzene, and tris(3-tert-butyl-4-hydroxy-5-methylbenzyl)isocyanurate, etc. Among the above compounds, tetrakis[methylene-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate]methane, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and 3,9-bis[2-{3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy}-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5,5]undecane are preferably used in the present invention. 3,9-bis[2-{3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy}-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5,5]undecane is particularly preferred. The above hindered phenol compounds can be used alone or in combination of two or more.

[0129] The content of the phenolic stabilizer is preferably 0.001 to 3.0 parts by weight, more preferably 0.01 to 2.0 parts by weight, and even more preferably 0.05 to 1.0 part by weight, based on 100 parts by weight of the components consisting of the components A and B.

[0130] The polycarbonate resin composition of the present invention may also be formulated with other heat stabilizers other than the above-mentioned phosphorus stabilizers and phenolic stabilizers. The above-mentioned other heat stabilizers are preferably used in combination with any one of these stabilizers and antioxidants, and particularly preferably in combination with both. As the above-mentioned other heat stabilizers, for example, lactone stabilizers represented by the reaction product of 3-hydroxy-5,7-di-tert-butyl-furan-2-one and o-xylene can be preferably exemplified (the details of the above-mentioned stabilizers are described in Japanese Patent Publication No. 7-233160). The above-mentioned compound is commercially available in the form of Irganox HP-136 (trademark, manufactured by CIBASPECIALTYCHEMICALS), and the compound can be used. In addition, stabilizers obtained by mixing the compound with various phosphite compounds and hindered phenol compounds are also commercially available. For example, Irganox HP-2921 manufactured by the above-mentioned company can be preferably exemplified. The above-mentioned pre-mixed stabilizers can also be used in the present invention. The content of the lactone stabilizer is preferably 0.0005 to 0.05 parts by weight, more preferably 0.001 to 0.03 parts by weight, based on 100 parts by weight of the components consisting of the components A and B.

[0131] In addition, as other stabilizers, sulfur-containing stabilizers such as pentaerythritol tetrakis (3-mercaptopropionate), pentaerythritol tetrakis (3-lauryl thiopropionate) and glycerol-3-stearyl thiopropionate can be exemplified. The above stabilizers are particularly effective when the resin composition is applied to rotational molding. The content of the above sulfur-containing stabilizer is preferably 0.001 to 0.1 parts by weight, and more preferably 0.01 to 0.08 parts by weight, relative to 100 parts by weight of the components consisting of component A and component B.

[0132] (ii) Release agent

[0133] The polycarbonate resin composition of the present invention may be formulated with a release agent to improve its productivity during molding and reduce deformation of the molded product. As the above-mentioned release agent, a known release agent can be used. For example, saturated fatty acid esters, unsaturated fatty acid esters, polyolefin waxes (polyethylene waxes, 1-olefin polymers, etc. Waxes modified by compounds containing functional groups such as acid modification can be used), silicone compounds, fluorine compounds (fluorinated oils represented by polyfluoroalkyl ethers, etc.), paraffin wax, beeswax, etc. can be cited. Among them, fatty acid esters can be cited as preferred release agents. The above-mentioned fatty acid esters are esters of aliphatic alcohols and aliphatic carboxylic acids. The above-mentioned aliphatic alcohols can be monohydric alcohols or polyhydric alcohols with a valence of more than two valences. In addition, the number of carbon atoms of the alcohol is in the range of 3 to 32, and more preferably in the range of 5 to 30. As the above-mentioned monohydric alcohol, for example, dodecanol, tetradecanol, hexadecanol, octadecyl alcohol, eicosanol, tetracosanol, cetyl alcohol and triacontanol can be exemplified. As the above-mentioned polyols, pentaerythritol, dipentaerythritol, tripentaerythritol, polyglycerol (triglycerol to hexaglycerol), dimethylolpropane, xylitol, sorbitol and mannitol can be mentioned. Polyols are more preferred in the fatty acid esters of the present invention. On the other hand, the aliphatic carboxylic acid preferably has 3 to 32 carbon atoms, and particularly preferably has 10 to 22 carbon atoms. As the aliphatic carboxylic acid, for example, saturated aliphatic carboxylic acids such as decanoic acid, undecanoic acid, dodecanoic acid, tridecanoic acid, tetradecanoic acid, pentadecanoic acid, hexadecanoic acid (palmitic acid), heptadecanoic acid, octadecanoic acid (stearic acid), nonadecanoic acid, behenic acid, eicosanoic acid and docosanoic acid, and unsaturated aliphatic carboxylic acids such as palmitoleic acid, oleic acid, linoleic acid, linolenic acid, eicosenoic acid, eicosapentaenoic acid and cetylene acid can be mentioned. The aliphatic carboxylic acid in the above preferably has 14 to 20 carbon atoms. Among them, saturated aliphatic carboxylic acids are preferred. Stearic acid and palmitic acid are particularly preferred. The above-mentioned aliphatic carboxylic acids such as stearic acid and palmitic acid are usually made from natural oils and fats such as animal fats represented by beef tallow and lard and plant fats and fats represented by palm oil and sunflower oil, so these aliphatic carboxylic acids are usually mixtures containing other carboxylic acid components with different carbon atoms. Therefore, in the manufacture of the fatty acid ester of the present invention, it is also preferred to use aliphatic carboxylic acids, especially stearic acid and palmitic acid, which are made from the above-mentioned natural oils and fats and are composed of a mixture containing other carboxylic acid components. The fatty acid ester can be any one of a partial ester and a full ester. However, when it is a partial ester, the hydroxyl value usually becomes high, which easily induces resin decomposition at high temperature, so it is more preferably a full ester. From the aspect of thermal stability, the acid value of the fatty acid ester of the present invention is preferably 20 or less, more preferably in the range of 4 to 20, and further preferably in the range of 4 to 12. It should be noted that the acid value can be substantially 0. In addition, the hydroxyl value of the fatty acid ester is more preferably in the range of 0.1 to 30. In addition, the iodine value is preferably 10 or less. It should be noted that the iodine value can be substantially 0. These properties can be obtained by the methods specified in JIS K0070.

[0134] The content of the release agent is preferably 0.01 to 4.0 parts by weight, more preferably 0.05 to 3.0 parts by weight, and even more preferably 0.1 to 2.5 parts by weight, based on 100 parts by weight of the components consisting of the components A and B.

[0135] (iii) Ultraviolet light absorber

[0136] The polycarbonate resin composition of the present invention may contain an ultraviolet absorber. Examples of the benzophenone series include 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octyloxybenzophenone, 2-hydroxy-4-benzyloxybenzophenone, 2-hydroxy-4-methoxy-5-sulfonic acid benzophenone, 2-hydroxy-4-methoxy-5-sulfonic acid trihydrobenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone-5-sodium sulfonate, bis(5-benzoyl-4-hydroxy-2-methoxyphenyl)methane, 2-hydroxy-4-n-dodecyloxybenzophenone, and 2-hydroxy-4-methoxy-2'-carboxybenzophenone. Among the benzotriazole series, for example, 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 2-(2-hydroxy-3,5-dicumylphenyl)phenylbenzotriazole, 2-(2-hydroxy-3-tert-butyl-5-methylphenyl)-5-chlorobenzotriazole, 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], 2-(2-hydroxy-3,5-di-tert-butylphenyl)benzotriazole, 2-(2-hydroxy-3,5-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2-hydroxy-3,5-di-tert-amylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 2-( Polymers having a 2-hydroxyphenyl-2H-benzotriazole skeleton such as 2-hydroxy-5-tert-butylphenyl)benzotriazole, 2-(2-hydroxy-4-octyloxyphenyl)benzotriazole, 2,2'-methylenebis(4-cumyl-6-benzotriazolephenyl), 2,2'-p-phenylenebis(1,3-benzoxazin-4-one) and 2-[2-hydroxy-3-(3,4,5,6-tetrahydrophthalimidomethyl)-5-methylphenyl]benzotriazole, copolymers of 2-(2'-hydroxy-5-methacryloyloxyethylphenyl)-2H-benzotriazole and a vinyl monomer copolymerizable with the monomer, and copolymers of 2-(2'-hydroxy-5-acryloyloxyethylphenyl)-2H-benzotriazole and a vinyl monomer copolymerizable with the monomer. Examples of hydroxyphenyltriazine-based phenols include 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-hexyloxyphenol, 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-methoxyphenol, 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-ethoxyphenol, 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-propoxyphenol, and 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-butoxyphenol.In addition, compounds in which the phenyl group of the above-mentioned compounds is 2,4-dimethylphenyl, such as 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl)-5-hexyloxyphenol, can be exemplified. Among the cyclic iminoesters, for example, 2,2′-p-phenylenebis(3,1-benzo Oxazine-4-one), 2,2'-(4,4'-diphenylene)bis(3,1-benzo Oxazine-4-one) and 2,2'-(2,6-naphthalene)bis(3,1-benzo Oxazine-4-one) etc.

[0137] Examples of cyanoacrylates include 1,3-bis-[(2′-cyano-3′,3′-diphenylacryloyl)oxy]-2,2-bis[(2-cyano-3,3-diphenylacryloyl)oxy]methyl)propane and 1,3-bis-[(2-cyano-3,3-diphenylacryloyl)oxy]benzene.

[0138] In addition, the above-mentioned ultraviolet absorber can also be a polymer type ultraviolet absorber obtained by copolymerizing the above-mentioned ultraviolet absorbing monomer and / or the light stabilizing monomer having a hindered amine structure with monomers such as alkyl (meth) acrylate by adopting the structure of a monomer compound capable of free radical polymerization. As the above-mentioned ultraviolet absorbing monomer, compounds containing a benzotriazole skeleton, a benzophenone skeleton, a triazine skeleton, a cyclic iminoester skeleton and a cyanoacrylate skeleton in the ester substituent of the (meth) acrylate can be preferably exemplified.

[0139] The content of the ultraviolet absorber is preferably 0.01 to 2.0 parts by weight, more preferably 0.02 to 1.5 parts by weight, and even more preferably 0.03 to 1.0 parts by weight, based on 100 parts by weight of the components consisting of the components A and B.

[0140] (iv) Core-shell graft polymer

[0141] The polycarbonate resin composition of the present invention may contain a core-shell graft polymer. The core-shell graft polymer is a graft copolymer obtained by copolymerizing a rubber component having a glass transition temperature of 10° C. or less as a core and one or more monomers selected from aromatic vinyl, cyanide vinyl, acrylate, methacrylate and vinyl compounds copolymerizable therewith as a shell.

[0142] As the rubber component of the core-shell graft polymer, butadiene rubber, butadiene-acrylic composite rubber, acrylic rubber, acrylic-silicone composite rubber, isobutylene-silicone composite rubber, isoprene rubber, styrene-butadiene rubber, chloroprene rubber, ethylene-propylene rubber, nitrile rubber, ethylene-acrylic rubber, silicone rubber, epichlorohydrin rubber, fluororubber and rubber components obtained by hydrogenating unsaturated bonds thereof are mentioned. From the point of view of the concern of generating harmful substances during combustion, rubber components that do not contain halogen atoms are preferred in terms of environmental load. The glass transition temperature of the rubber component is preferably below -10°C, more preferably below -30°C. As the rubber component, butadiene rubber, butadiene-acrylic composite rubber, acrylic rubber and acrylic-silicone composite rubber are particularly preferred. Composite rubber refers to a rubber obtained by copolymerizing two rubber components or a rubber polymerized into an IPN structure that is entangled with each other in an inseparable manner. In the core-shell graft polymer, the particle size of the core is preferably 0.05 to 0.8 μm, more preferably 0.1 to 0.6 μm, and further preferably 0.15 to 0.5 μm in terms of weight average particle size. When it is in the range of 0.05 to 0.8 μm, better impact resistance can be achieved.

[0143] As the aromatic vinyl of the vinyl compound copolymerized as the shell of the core-shell graft polymer in the rubber component, styrene, α-methylstyrene, p-methylstyrene, alkoxystyrene, halogenated styrene, etc. can be mentioned. In addition, as acrylates, methyl acrylate, ethyl acrylate, butyl acrylate, cyclohexyl acrylate, octyl acrylate, etc. can be mentioned, and as methacrylates, methyl methacrylate, ethyl methacrylate, butyl methacrylate, cyclohexyl methacrylate, octyl methacrylate, etc. can be mentioned, and methyl methacrylate is particularly preferred. Among these, methacrylates such as methyl methacrylate are particularly preferred as essential components. This is because: the core-shell graft polymer has excellent affinity with the aromatic polycarbonate resin, so that more rubber components are present in the resin, and the good impact resistance of the aromatic polycarbonate resin is more effectively exerted. As a result, the impact resistance of the resin composition becomes good. More specifically, the methacrylate preferably contains 10% by weight or more of the grafted component (in the case of a core-shell polymer, in the shell 100% by weight), and more preferably contains 15% by weight or more. The elastic polymer containing a rubber component having a glass transition temperature of 10°C or less can be produced by any polymerization method including bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization, and the copolymerization method can be a one-step grafting or a multi-step grafting. In addition, it can also be a mixture with a copolymer of only the grafted component generated as a by-product during the production. In addition, as a polymerization method, in addition to the general emulsion polymerization method, soap-free polymerization using an initiator such as potassium persulfate, seed polymerization, two-step swelling polymerization, etc. can also be cited. In the suspension polymerization method, a method of controlling the particle size by keeping the aqueous phase and the monomer phase separately and accurately supplying them to a continuous disperser and utilizing the rotation speed of the disperser, and a method of controlling the particle size by supplying the monomer phase to an aqueous liquid having a dispersibility through a fine pore or porous filter having a diameter of several to several tens of μm in a continuous production method, etc. In the case of a core-shell graft polymer, the reaction of the core and the shell can be one step or multiple steps.

[0144] The above polymers are already commercially available and can be easily obtained. For example, as a rubber component, products containing butadiene rubber as a main component include Kane Ace M series manufactured by Kaneka Co., Ltd. (e.g., M-711 with methyl methacrylate as a main component as a shell component, M-701 with methyl methacrylate and styrene as a main component as a shell component, etc.), METABLEN C series manufactured by Mitsubishi Rayon Co., Ltd. (e.g., C-223A with methyl methacrylate and styrene as a main component as a shell component, etc.), E series (e.g., E-870A with methyl methacrylate and styrene as a main component as a shell component, etc.), PARALOID EXL series manufactured by Dow Chemical Co., Ltd. (e.g., EXL-2690 with methyl methacrylate as a main component as a shell component, etc.), and products containing acrylic rubber or butadiene-acrylic composite rubber as a main component include W series (e.g., W-600A with methyl methacrylate as a main component as a shell component, etc.), PARALOID The EXL series (for example, EXL-2390 whose shell component is mainly composed of methyl methacrylate) includes products whose rubber component is mainly composed of acrylic-silicone composite rubber, and products sold under the trade name such as METABLEN S-2501 manufactured by Mitsubishi Rayon Co., Ltd. whose shell component is mainly composed of methyl methacrylate, or SX-200R whose shell component is mainly composed of acrylonitrile / styrene.

[0145] (v) Other resins

[0146] The polycarbonate resin composition of the present invention may also contain other resins in a small proportion within the range in which the effects of the present invention are exerted. Examples of the other resins include AES resins, ASA resins, polyester resins, polyamide resins, polyimide resins, polyetherimide resins, polyurethane resins, silicone resins, polyphenylene ether resins, polyphenylene sulfide resins, polysulfone resins, polymethacrylate resins, phenol resins, fluororesins, and the like.

[0147] (vi) Dyes and pigments

[0148] The polycarbonate resin composition of the present invention can provide a molded product that further contains various dyes and pigments and embodies various designs. By adding a fluorescent whitening agent or other fluorescent dyes that emit light, a better design effect of generating luminescent colors can be given. In addition, a polycarbonate resin composition that is colored with a very small amount of dyes and pigments and has a bright color can also be provided.

[0149] As the fluorescent dye (including fluorescent whitening agent) used in the present invention, for example, coumarin fluorescent dye, benzopyran fluorescent dye, perylene fluorescent dye, anthraquinone fluorescent dye, thioindigo fluorescent dye, xanthene fluorescent dye, xanthone fluorescent dye, thioxanthene fluorescent dye, thioxanthene fluorescent dye, thiazine fluorescent dye and diaminostilbene fluorescent dye can be mentioned. Among these, coumarin fluorescent dye, benzopyran fluorescent dye and perylene fluorescent dye, which have good heat resistance and little deterioration during the molding of polycarbonate resin, are preferred.

[0150] Examples of dyes other than the above-mentioned bluing agents and fluorescent dyes include perylene dyes, coumarin dyes, thioindigo dyes, anthraquinone dyes, thioxanthone dyes, ferrocyanides such as Prussian blue, perinone dyes, quinoline dyes, quinacridone dyes, dimethicone dyes, and the like. Oxazine dyes, indolinone dyes and phthalocyanine dyes, etc. In addition, the resin composition of the present invention can be combined with a metallic pigment to obtain a better metallic color. As the metallic pigment, it is preferred that various plate-like fillers have a metal film or a metal oxide film.

[0151] The content of the dye and pigment is preferably 0.00001 to 1 part by weight, more preferably 0.00005 to 0.5 part by weight, based on 100 parts by weight of the components consisting of the components A and B.

[0152] (vii) Flame retardant

[0153] The polycarbonate resin composition of the present invention may contain various compounds that are conventionally known as flame retardants for thermoplastic resins, particularly polycarbonate resins, and more preferably, (i) halogen flame retardants (e.g., brominated polycarbonate compounds, etc.), (ii) phosphorus flame retardants (e.g., monophosphate compounds, phosphate oligomer compounds, phosphonate oligomer compounds, phosphazene oligomer compounds, phosphoramide compounds, and phosphazene compounds, etc.), (iii) metal salt flame retardants (e.g., organic sulfonic acid alkali (earth) metal salts, borate metal salt flame retardants, and stannate metal salt flame retardants, etc.), and (iv) organosilicon flame retardants composed of organosilicon compounds. It should be noted that the compound used as a flame retardant not only improves flame retardancy, but also brings about improvements in antistatic properties, fluidity, rigidity, and thermal stability, etc., depending on the properties of each compound.

[0154] The content of the flame retardant is preferably 0.01 to 30 parts by weight, more preferably 0.05 to 28 parts by weight, and further preferably 0.08 to 25 parts by weight relative to 100 parts by weight of the components consisting of component A and component B. When the content of the flame retardant is less than 0.01 parts by weight, sufficient flame retardancy may not be obtained, and when it exceeds 30 parts by weight, mechanical properties may be greatly reduced.

[0155] (viii) White pigment for high light reflection

[0156] The polycarbonate resin composition of the present invention may be formulated with a white pigment for high light reflection to impart a light reflection effect. Examples of the white pigment include zinc sulfide, zinc oxide, barium sulfate, calcium carbonate, calcined kaolin, and the like. The content of the white pigment for high light reflection is preferably 1 to 30 parts by weight, more preferably 3 to 25 parts by weight, relative to 100 parts by weight of the components consisting of component A and component B. It should be noted that two or more white pigments for high light reflection may be used in combination.

[0157] (ix) Other additives

[0158] In addition, the resin combination of the present invention can be matched with a smaller proportion of additives known to be used for giving various functions to molded products and improving characteristics. These additives are common amounts of compounding as long as they do not damage the purpose of the present invention. As the above-mentioned additives, lubricants (such as PTFE particles), colorants (such as pigments and dyes such as carbon black), light diffusing agents (such as acrylic acid cross-linked particles, silicon cross-linked particles, very thin glass fragments, calcium carbonate particles), fluorescent dyes, inorganic phosphors (such as phosphors with aluminate as mother crystals), antistatic agents, nucleating agents, inorganic and organic antibacterial agents, photocatalyst antifouling agents (such as micro-particle titanium oxide, micro-particle zinc oxide), free radical generators, infrared absorbers (heat ray absorbers) and photochromic agents etc. can be enumerated.

[0159] <Method for preparing polycarbonate resin composition>

[0160] The polycarbonate resin composition of the present invention is prepared by mixing the above-mentioned components simultaneously or in any order using a mixer such as a drum, a V-type mixer, a Nauta mixer, a Banbury mixer, a mixing drum, an extruder, etc. As a mixer, it is preferred to use a twin-shaft extruder for melt kneading, and it is preferred to use a side feed hopper or the like to supply any component to the other melt-mixed components from the second supply port as needed. The extruded resin as described above is directly cut and pelletized, or the strands are formed and then cut and pelletized using a granulator. In the case where it is necessary to reduce the influence of external dust, etc. during pelletization, it is preferred to clean the atmosphere around the extruder. The shape of the pellets obtained can be a general shape such as a cylinder, a prism and a sphere, and is more preferably a cylinder. The diameter of the cylinder is preferably 1 to 5 mm, more preferably 1.5 to 4 mm, and more preferably 2 to 3.5 mm. On the other hand, the length of the cylinder is preferably 1 to 30 mm, more preferably 2 to 5 mm, and more preferably 2.5 to 4 mm.

[0161] <Molded article composed of the polycarbonate resin composition of the present invention>

[0162] The polycarbonate resin composition of the present invention can be manufactured into various products by injection molding the pellets usually obtained by the above method. In the above injection molding, not only the usual molding method can be used, but also injection molding methods such as injection compression molding, injection stamping molding, gas-assisted injection molding, foam molding (including molding based on supercritical fluid injection), insert molding, in-mold coating molding, heat-insulating metal mold molding, rapid heating and cooling metal mold molding, two-color molding, sandwich molding and ultra-high-speed injection molding can be used appropriately according to the purpose to obtain molded products. The advantages of these various molding methods are well known. In addition, molding can be selected from either the cold runner method or the hot runner method.

[0163] The inventors of the present invention believe that the best mode of the present invention is to focus on the preferred ranges of the above-mentioned requirements, and representative examples thereof are described in the following embodiments. Of course, the present invention is not limited to these modes.

[0164] Example

[0165] The present invention will be further described below with reference to Examples. It should be noted that the evaluation was carried out by the following method.

[0166] (i) Linear expansion coefficient

[0167] After annealing the ISO tensile test piece obtained by the following method (dried at 110°C × 1h), a 5mm square test piece was cut out. The linear expansion coefficient of the test piece at -30°C to 80°C was measured at a heating rate of 2°C / min using a linear expansion coefficient measuring device "TMA4000SE" manufactured by NETZSCH, with the flow direction of the resin during injection molding as the measurement direction. The polycarbonate resin composition of the present invention needs to reduce the linear expansion coefficient of the C component calculated by the following formula by 0.15×10 ―5 / ℃ or above.

[0168] Reduction value of linear expansion coefficient per 1 part by weight of component C = (linear expansion coefficient of the component consisting of components A and B - linear expansion coefficient of the polycarbonate resin composition of the present invention) / content of component C

[0169] (ii) Appearance of molded product

[0170] After obtaining the ISO tensile test piece by the following method, the molding machine was stopped for 10 minutes under the same conditions as the following method, and the molten resin was retained in the molding machine barrel. After stopping the molding machine for 10 minutes, the molding was restarted, and the ISO tensile test piece of the second injection from the remolding was obtained. The molding machine before stopping was regarded as a continuous molded product, and the second injection from the remolding was regarded as a retained molded product, and the appearance of each was evaluated by visual inspection. It should be noted that the evaluation was implemented according to the following criteria.

[0171] ○: Neither the continuous molded product nor the retained molded product had any appearance defects.

[0172] △: The continuous molded product has no appearance defects, but the retained molded product has appearance defects such as silver streaks.

[0173] ×: Both the continuous molded products and the retained molded products had appearance defects such as silver streaks.

[0174] (iii) Deflection temperature under load

[0175] The deflection temperature under load (load 1.80 MPa) was measured in accordance with ISO 75-1 and ISO 75-2 using an ISO bending test piece obtained by the following method. The polycarbonate resin composition of the present invention needs to have a deflection temperature under load of 90° C. or higher.

[0176] (iv) Liquidity

[0177] The pellets obtained by the following method were used to measure the Archimedean spiral length of a flow path thickness of 2 mm and a flow path width of 8 mm using an injection molding machine [SE130EV-A manufactured by Sumitomo Heavy Industries, Ltd.] The measurement was performed at a barrel temperature of 260° C., a metal mold temperature of 70° C., and an injection pressure of 98 MPa. The polycarbonate resin composition of the present invention needs to have a spiral length of 20 cm or more.

[0178] [Examples 1 to 19, Comparative Examples 1 to 8]

[0179] A mixture of the components listed in Tables 1 and 2 except the ABS resin of component B and the silicate mineral of component C was supplied from the first supply port of the extruder. The above mixture was obtained by mixing using a V-type mixer. The ABS resin of component B and the silicate mineral of component C were supplied separately from the second supply port using a side feed hopper. The pellets were melt-kneaded in a vented twin-screw extruder (TEX30α-38.5BW-3V, Japan Steel Works, Ltd.) at a screw speed of 230 rpm, a discharge volume of 25 kg / h, and an exhaust vacuum of 3 kPa to obtain pellets. It should be noted that the extrusion temperature was implemented at 260°C from the first supply port to the die head. The obtained pellets were dried at 110°C using a hot air circulation dryer for 6 hours, and then molded into ISO bending test pieces and ISO tensile test pieces for evaluation using an injection molding machine (barrel temperature 260°C, metal mold temperature 60°C), and each evaluation was carried out. The results are shown in Tables 1 and 2.

[0180] In addition, the following materials were used as raw materials.

[0181] (A ingredient)

[0182] A-1: Aromatic polycarbonate resin (polycarbonate resin powder having a viscosity average molecular weight of 19,800 produced from bisphenol A and phosgene by a conventional method, Panlite L-1225WX (product name) manufactured by Teijin Limited)

[0183] A-2: Aromatic polycarbonate resin (polycarbonate resin powder having a viscosity average molecular weight of 22,400 produced from bisphenol A and phosgene by a conventional method, Panlite L-1225WP (product name) manufactured by Teijin Limited)

[0184] A-3: Aromatic polycarbonate resin (polycarbonate resin powder having a viscosity average molecular weight of 16,000 produced from bisphenol A and phosgene by a conventional method, Panlite CM-1000 (product name) manufactured by Teijin Limited)

[0185] (Component B)

[0186] B-1: ABS resin (SO4 2- Content 3.4ppm, PO4 3- Content 0.01ppm, GA-704 (product name) manufactured by Japan A&L Co., Ltd.

[0187] B-2: ABS resin (SO4 2- Content 4.0ppm, PO4 3- Content 0.01ppm, SXH-330 (product name) manufactured by Japan A&L Co., Ltd.

[0188] B-3: ABS resin (SO4 2- Content 3.2ppm, PO4 3- Content 0.01ppm, AF-3510 (product name) manufactured by Formosa Chemical & FibreCorp

[0189] B-4: ABS resin (SO4 2- Content 0.02ppm, PO4 3- Content 0.01ppm, AT-05 (product name) manufactured by Japan A&L Co., Ltd.

[0190] B-5: ABS resin (SO4 2- Content 5.1ppm, PO4 3- Content 5.2ppm, ABS250 (product name) manufactured by INEOS ABS CO LTD)

[0191] B-6: ABS resin (mixture of B-1 and B-4 (weight ratio 1:1) SO4 2- Content 1.7ppm, PO4 3-Content 0.01ppm)

[0192] B-7: ABS resin (mixture of B-1 and B-5 (weight ratio 4:1) SO4 2- Content 3.7ppm, PO4 3- Content 1.1ppm)

[0193] B-8: ABS resin (mixture of B-1 and B-4 (weight ratio 1:5) SO4 2- Content 0.6ppm, PO4 3- Content 0.01ppm)

[0194] B-9: ABS resin (mixture of B-1 and B-5 (weight ratio 2:1) SO4 2- Content 4.0ppm, PO4 3- Content 1.8ppm)

[0195] (Component C)

[0196] C-1: Talc (Victory Light TK-RC (product name) manufactured by Shengguangshan Mining Co., Ltd.)

[0197] C-2: Mica (GM-6 (product name) manufactured by Kinseimatec Co., Ltd.)

[0198] C-3: Wollastonite (SH-1800 (product name) manufactured by Kinseimatec Co., Ltd.)

[0199] (Component D)

[0200] D-1: triethyl phosphonoacetate (JC-224 (product name) manufactured by Johoku Chemical Industry Co., Ltd., acid value 0.08 mgKOH / g)

[0201] D-1: triethyl phosphonoacetate (manufactured by Solvay, acid value 0.39 mgKOH / g) (other ingredients)

[0202] E-1: Phenolic heat stabilizer (octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, Irganox 1076 (product name) manufactured by BASF Japan Co., Ltd.)

[0203] E-2: Butadiene core-shell graft polymer (a graft copolymer having a core-shell structure in which the core contains 60 wt% of butadiene rubber as the main component and the shell contains 40 wt% of methyl methacrylate as the main component, KaneAce M-711 (product name) manufactured by Kaneka Co., Ltd.)

[0204] E-3: Polyethylene terephthalate resin (TRN-MTJ (product name) manufactured by Teijin Limited)

[0205] E-4: Carbon black (manufactured by Koshigaya Chemicals Co., Ltd.: ROYALBLACK RB90003S (product name))

[0206]

[0207] [Table 2]

[0208]

[0209] From the above table, it can be seen that a polycarbonate resin composition having excellent fluidity and heat resistance and a low linear expansion coefficient can be obtained by making the polycarbonate resin contain predetermined amounts of a specific ABS resin and a silicate mineral.

Claims

1. A polycarbonate resin composition, characterized in that With respect to 100 parts by weight of a component consisting of 20 to 90 parts by weight of (A) polycarbonate resin, i.e., component A, and 80 to 10 parts by weight of (B) ABS resin, i.e., component B, containing 5 to 45 parts by weight of (C) silicate mineral, i.e., component C, the SO4 in component B is 2- The content is above 1ppm, and PO4 3- The content is less than 1.5ppm.

2. The polycarbonate resin composition according to claim 1, characterized in that The phosphorus-based stabilizer (D), that is, component D, is contained in an amount of 0.001 to 1 part by weight based on 100 parts by weight of the components consisting of components A and B.

3. The aromatic polycarbonate resin composition according to claim 2, characterized in that: The component D is a phosphonic acid ester having an acid value of 0.01 to 0.30 mgKOH / g.

4. The thermoplastic resin composition according to claim 3, characterized in that Component D is triethyl phosphonoacetate. 5 . A molded article formed from the polycarbonate resin composition according to claim 1 .

Citation Information

Patent Citations

  • Manufacturing method of polycarbonate resin

    JP1993306336A

  • Aromatic copolycarbonate

    JP1994172508A

  • 3-arylbenzofuranone as stabilizer

    JP1995233160A

  • Aromatic polycarbonate composition

    JP1996027370A

  • Molding material for optical recording medium

    JP2001055435A